Improving the Performance of Solar Voltage Regulator Using Fuzzy Supervisory Controller (FSC) - داوود محسن; ديوب محمد; ونوس محمد (Latakia University Journal -Engineering Sciences Series, 2021)
This paper includes a study of modern control systems , and focuses on the system that uses both Fuzzy Logic Control (FLC) and Proportional Integral Differential control (PID). which called the (Fuzzy Supervisory Controller)FSC, this system will be used in the solar voltage regulator to get the best response parameters. The voltage generated by the solar panel has been adjusted using a Buck-Boost converter , which controlled using (FSC) controller. This system is also simulated using the Simulink environment in MATLAB. The initial PID parameters have been calculated using Ziegler-Nichols rules, and it has been used in the solar voltage regulator. Fuzzy Logic controller rules have also been set to simultaneously calibrate the PID parameters according to the error and change in error. Then the comparison has made between the results of using the both controller (PID) and (FSC). The results have proved that the using of (FSC) gives better results than (PID) and showed a clear improvement in the output curve for all response parameters .